Review of Vocational Education Curriculum in the Fourth Industrial Revolu-tion and Contribution to Rural Development - Misbachul Munir; Ella Anastasya Sinambela; Siti Nur Halizah; Rafadi Khan Khayru; Vatosoa Mendrika (Journal of Social Science Studies (JOS3), 2022)
The industrial revolution 4.0 is an opportunity as well as a threat for all sectors. The era of the The industrial revolution 4.0 is an opportunity as well as a threat for all sectors. The era of the industrial revolution 4.0 changed the concept of work, work structure, and competencies needed by the world of work. The changes made are not only in the way of teaching, but are far more essential, namely changes in the perspective on the concept of education itself, one of which is vocational education. This study aims to determine the application of the vocational curriculum to be able to compete in the Industrial Revolution 4.0 Era. The method used in writing this article is the literature analysis method. The results show that in this new paradigm, the teacher's role remains strategic as a designer and implementer of learning, more as a facilitator and motivator so that students are active in an effective and optimal learning process. Curriculum preparation requires opinions from several parties such as academia, government and industry. curriculum adjustments, can be rebranded through direct studies to see the needs of human resources in the industry or through comparative studies to more advanced educational institutions both at home and abroad. In addition, vocational education is also expected to be implemented by building villages. Vocational graduates are expected to be able to provide innovative solutions to solve problems that exist in the village. Vocational education support to develop villages requires cooperation from various parties.